Redefinition of the Yeast Two-Hybrid System in Dialogue with Changing Priorities in Biological Research - Ilya G. Serebriiskii; Vladimir Khazak; Erica A. Golemis (BioTechniques)
Examination of the pattern of reagent creation and application in the two-hybrid system since 1989 reveals the expansion of a simple core technology to address increasingly sophisticated problems in protein interaction. As the technology has matured, its clear suitability for large-scale proteomic projects has made a major focus of its application the generation of global organismal protein interaction networks. In an inversion of emphasis, the increasing availability of such information now provides a master plan with the potential to specify the most promising directions for biological investigations (i.e., by directing the physiological validation of predicted critical protein-protein interactions). Recent derivatives of the two-hybrid system enable the targeting of such key interactions by facilitating the identification of essential amino acids conferring protein interaction specificity and of small molecules that selectively disrupt defined interaction pairs. Finally, the creation of mammalian expression systems based on two-hybrid principles became a new tool to create and probe novel biological systems. Taken in sum, this trajectory emphasizes the point that the creation of tools and the evolution of the idea of what is an interesting biological problem are in intimate dialogue.